2008
DOI: 10.5964/ijpr.v2i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Do Psychological Birth Order Positions Predict Future Time Orientation in Romantic Relationships?

Abstract: Psychological birth order was examined as predictor of future time orientation in romantic relationships among Turkish people using a Turkish version (Kalkan, 2005) of the White-Campbell Psychological Birth Order Inventory (Campbell, White & Stewart, 1991) and the Future Time Orientation in Romantic Relationships Scale (Öner, 2000). A total of 407 university students from Ondokuz Mayıs University participated in the study. The results of hierarchical multiple regression analyses indicated that psychologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
2
0
5
Order By: Relevance
“…In a study conducted by Kalkan (2008), the effect of family related factors on future time orientation was discussed. Research pointed out that parents' manner of approaching the child and individual's self-perception within the family influence temporary or long-term romantic relationship orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Kalkan (2008), the effect of family related factors on future time orientation was discussed. Research pointed out that parents' manner of approaching the child and individual's self-perception within the family influence temporary or long-term romantic relationship orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Romantic relationships, then, involve the sum of previous childhood identifications in which the attachment dimensions and socio economic status of family play a crucial role in formation and cultural conceptualization of being about relations (Steinberg, 1985). The research conducted by Kalkan (2008) discussed the influence of familial factors in future time orientation in romantic relationships. That research suggested that the parents' approach and self-perception of the individual within the family is effective on temporary or long-term romantic relationship orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Orientasi masa depan berpusat di kepentingan seseorang tentang masa depannya. Orientasi masa depan dapat diartikan sebagai pemikiran dan perencanaan tentang masa depan (Malmberg &Norrgard dalam Dorham, 2005 ;Putri, 2010) dan sebagai tempat untuk mengelola dan mengantisipasi kejadian di masa depan (Gjesma, dalam Öner, 2000;Kalkan, 2008, Putri 2010.…”
Section: Pendahuluanunclassified
“…Psikolojik doğum sırası ile çocukluk çağı örselenme yaşantıları (Karadeniz, 2008), stresle başa çıkma stratejileri (Kalkan ve Koç, 2008), ana babaya bağlanma (Kalkan ve Odacı, 2010), karşı cinsle ilişkide sosyal yetkinlik beklentisi (Başaranoğlu, 2011), psikolojik sağlamlık (Oktan, Odacı ve Çelik, 2014), gelecek zaman romantik ilişkilerde uyum (Kalkan, 2008a), mesleki ilgi (White, Campbell, Stewart, Davies & Pilkington, 1997), algılanan başetme kaynakları (Pilkington, White & Matheny, 1997) ve akıldışı ilişki inançları (Kalkan, 2008b)gibi değişkenler ile arasında anlamlı ilişki olduğu bulunmuştur.…”
Section: Introductionunclassified
“…Bununla birlikte, kendini büyük çocuk konumunda algılayanların, karşı cinsten bireylerle ilişkiyi devam ettirebilme, ortanca çocuk konumunda algılayanların ise ilişkiyi bitirebilme noktasında daha yetkin olduğu bulunmuştur (Başaranoğlu, 2011). Kalkan (2008a) psikolojik doğum sırası ile romantik ilişkilerdeki uyumu araştırırken büyük çocuk, ortanca çocuk ve tek çocuk psikolojik doğum sıralarının gelecek zaman romantik ilişkilerdeki uyumu yordadığını tespit etmiştir. Cinsiyet, gerçek doğum sırası ve küçük çocuk psikolojik doğum sırasının gibi değişkenlerin gelecek zaman romantik ilişkilerde uyumu yordamadığı görülmüştür.…”
Section: Introductionunclassified